Impact of Early Detection and Treatment on the Prognosis of Endometrial Cancer in High-Risk Populations - Sajida Razzaq, Sofia Manzoor, Sadia Dilawar, Lubna Malik, Mahpara Shaukat, Arooj Mushtaq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Endometrial cancer is a common gynecologic malignancy whose prognosis largely depends on the stage at diagnosis and the timeliness of treatment. Objective: This study aimed to assess the effect of early detection and prompt treatment on the prognosis of endometrial cancer among high-risk patients. Methodology: This retrospective observational study was conducted at Sir Ganga Ram Hospital, Lahore from November 2022 to May 2023. It included 165 female patients with histologically confirmed endometrial carcinoma. Patients were categorized into two groups: the early detection and treatment group (Stage I–II, treated within four weeks; n = 92) and the delayed detection and treatment group (Stage III–IV or treated after four weeks; n = 73). Results: The mean age of the study population was 58.7 ± 9.8 years, with obesity (59.4%) and diabetes (46.1%) being the most prevalent comorbidities. Endometrioid adenocarcinoma was the most common histological subtype (76.4%). The three-year overall survival rate was 91.3% in the early group compared to 63.0% in the delayed group (p < 0.001). Disease-free survival was also significantly higher in the early group (87.0% vs. 55.0%, p = 0.002). Recurrence occurred in 11.9% of early cases and 32.9% of delayed cases. Treatment-related complications were more frequent in the delayed group (21.9% vs. 9.8%). Conclusion: It is concluded that early detection and timely treatment significantly improve survival and reduce recurrence in endometrial cancer, particularly among high-risk women. Delayed diagnosis or initiation of therapy adversely affects prognosis and increases treatment-related morbidity. Keywords: Endometrial cancer, early detection, prognosis, high-risk populations, survival, treatment delay